What will be the impact of legalizing medical cannabis on economic effects in Japan? : analysis of case study in Germany and USA, Canada, Thailand. - Yuki Matsushita (Chulalongkorn University, 2020)
In recent years, cannabis has been legalized all over the world. Countries around the world are turning into cannabis legalization. As a result, in 2018, the WHO Expert Committee on Drug Dependence recommended the redesignation of cannabis, taking into account evidence of medical use (Mayor, 2019). Until today, the medical cannabis (MMJ) program has started in both high- and middle-income countries, including Canada, Colombia, Chile, Germany, Israel, Italy, Jamaica, the Netherlands, Switzerland, Thailand, the United Kingdom, Uruguay, and more than 30 states in the United States. In this study, I will consider the advantages and disadvantages of accepting medical cannabis with several cases of each country. There also be advised how Japanese government on regulating medical cannabis. As a result, it is necessary to discuss the liberalization of cannabis and the use of medical cannabis separately to prevent social turmoil when implementing cannabis-related policies in Japan. States also need to assess how much cannabis use can be regulated to minimize risk.